The Effect of Earnings Per Share (EPS), Price Earnings Ratio (PER), and Dividend Payout Ratio (DPR) on the Stock Price of PT Adaro Energy Indonesia Tbk - Feriadi, Felix; Widjaja, Indra; Evangelio, Rogue S (Ilomata International Journal of Tax and Accounting, 2024)
This study examines the influence of critical financial indicators on the stock price of PT Adaro Energy Indonesia Tbk, with particular emphasis on Earnings Per Share (EPS), Price Earnings Ratio (PER), and Dividend Payout Ratio (DPR) from 2008 to 2023. In the context of escalating global economic integration, organizations encounter significant competitive challenges, rendering financial performance analysis essential for strategic decision-making. Although much study has been conducted on financial ratios, limited studies comprehensively investigate the collective impact of these factors on stock prices within Indonesia's energy industry, particularly over an extended data range. This study employs a quantitative research methodology and multiple regression analysis, revealing that EPS strongly affects stock prices, underscoring its vital importance in shareholder value. The data demonstrate that both EPS and PER exert a substantial influence on stock prices independently, but DPR has no meaningful impact. EPS, PER, and DPR jointly exert a substantial effect, accounting for 65.6% of the volatility in stock prices. These insights enhance the comprehension of the significance of financial measures in stock valuation, offering strategic considerations for investors and corporate management in their decision-making processes.